LEGAL PROTECTION FOR WORKERS WHO HAVE TERMINATION OF EMPLOYMENT DUE TO FORCE MAJEURE - Yanuarko, Fajar; Setiasih, Herma (Acitya Wisesa: Journal of Multidisciplinary Research, 2022)
The purpose of this research is to find out the level of regulation conformity regarding the termination of employment due to Force Majeure in Indonesia in the form of legal protection and juridical consequences based on governing termination regulations of employment due to force mejaeure in order to fulfill the workers’ rights caused by layoffs. This research discusses the suitability of arrangements regarding workers who experience termination of employment due to Force Majeure in Indonesia with ideal legal protection and legal consequences of arrangements for employment termination implemented because of Force Majeure. The type of research used is normative legal research, is legal research that examines document studies using statutory regulations, court decisions, legal theory, and scholars’ opinions. The research result indicate that legal protection for workers who have been terminated due to Force Majeure has been reflected in Law 13 of 2003 concerning Manpower, but in order to create a positive law regarding forms of legal protection for workers who have been laid off, there must be clearer arrangements regarding the rights to workers in the future.